Review on Advanced Control Technique in Batch Polymerization Reactor of Styrene - Abdul Halim, Dayang Nur Adila; Abdul Sata, Suhairi (2013)
Polymerization process have a nonlinear nature since it exhibits a dynamic behavior throughout the process. Therefore, accurate modeling and control technique for the nonlinear process needs to be obtained.